AN APPLICATION OF GHARAVASADHAMMA 4 IN FAMILY DEVELOPMEN OF BAN KRONG PRAP COMMUNITY, KHLONG NOI SUBDISTRICT, CHAI BURI DISTRICT, SURAT THANI PROVINCE - Sangkham , Phonchai; ., Phrakru Kosolattakit; ., Phrakru Kositwattananukul; ., Phrakru Wichitsilachan; ., Phrakru Prasutphothikun (Journal of MCU Nakhondhat, 2024)
The objectives of the study were 1) To study the concept of family development of the Ban Klong Prap community, Klong Noi Subdistrict, Chaiburi District, Surat Thani Province, 2) To investigate the principle of Garavasadhamma 4 in the Theravada Buddhist scriptures, 3) To apply the principle of Garavasadhamma 4 in the development of the family of the Ban Klong Prap community, Klong Noi Subdistrict, Chaiburi District, Surat Thani Province. It isa qualitative research using in-depth interviews and presented in a descriptive writing. Findings were as follows: 1) The concept of family development is to promote the family to have a good quality of life between father, mother, children and the clan to be sustainable and stable. It focuses on promoting careers so that the family can rely on themselves, promoting health for family members when they are sick or entering old age, and promoting mental strength with morality and ethics to develop the mind. 2) The principle of Garavasadhamma 4 that appear in the Theravada Buddhist scriptures are the principles of teaching for layman’s household life, namely, truthfulness, honesty, self-control, patience, and generosity. They are teachings based on the path of household life to lead to family warmth. 3) The application of the principle of Garavasadhamma 4 makes living together in the family and with other people happy, without disputes, with a progressive life without defects and free from vices, able to perform duties effectively and creating happiness and unity for the family. Therefore, applying the principle of Garavasadhamma 4 to solve family problems is a way to help dissolve family conflicts, resulting in family members living together in warmth, and society and the country developing well.